Analisis Pengaruh Fraud Pentagon Terhadap Potensi Kecurangan Laporan Keuangan dengan Model Beneish M-Score Pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2022–2024 - Gracia Monica Silalahi; Elsa Imelda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine and analyze the effect of the Fraud Pentagon on the potential for financial statement fraud in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The potential for financial statement fraud is proxied by the Beneish M-Score model, while the Fraud Pentagon is measured through Financial Stability, Financial Target, External Pressure, Monitoring Effectiveness, Nature of Industry, Change in Auditor, Change of Director, and Frequent Number of CEO’s Picture. The research subjects were selected using a purposive sampling method based on predetermined criteria, resulting in 56 companies with a total of 135 observational data. This study utilizes secondary data obtained from the companies’ annual financial statements. Data analysis was conducted using multiple linear regression with the Statistical Package for the Social Sciences (SPSS) program version 27. The results indicate that External Pressure has a negative and significant effect on the potential for financial statement fraud, while Nature of Industry has a positive and significant effect on the potential for financial statement fraud. Meanwhile, Financial Stability, Financial Target, Monitoring Effectiveness, Change in Auditor, Change of Director, and Frequent Number of CEO’s Picture do not have a significant effect on the potential for financial statement fraud. These findings indicate that not all elements within the Fraud Pentagon theory are able to explain the potential for financial statement fraud in property and real estate sector companies. The results of this study are expected to provide useful insights for investors, creditors, auditors, and company management in identifying the risk of financial statement fraud as well as improving the effectiveness of supervision and corporate governance.